Infectious bronchitis in Brazil - Olofsson, Cecilia (2012)
Infectious Bronchitis (IB) is a highly contagious viral respiratory and production depressant disease distributed world wide. The disease is caused by the Infectious Bronchitis Virus (IBV), a positive RNA strand Avian Coronavirus within the genus Gammacoronavirus. Due to a combination of high mutation rate and a tendency of recombination a constant emergence of new genotypes and serotypes is seen. In Brazil, a country with an extensive poultry production and major problems with disease control, the diversity of circulating strains are wide and outbreaks of clinical disease despite intensive use of vaccines are common. The aim of this study was to investigate the presence of IBV and to identify genotypes of isolated IBVs in a limited number of layer flocks in Bastos, São Paulo, as part of the screening for circulating genotypes in the country. As a minor part the Biosecurity measures (precautions) was observed. In addition, a literature study was performed on IB and IBV. Organ samples from four farms were collected as pools of trachea, lungs, kidneys, reproductive tract and enteric content and were analyzed using Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). Over fifty percent of the samples were positive for IBV and three samples were identified as 4/91-genotype using Genotype-specific PCR. Due to problems with the RT-PCR that was targeting part of the S1-gene, the genotypes of the rest of the positive samples could not be determined using DNA sequencing. They were instead identified as not belonging to Massachusetts, D274 or 4/91 genotypes using Genotype-specific RT-PCR. Considering the results of previous studies in Brazil stating that a national Brazilian Variant dominates, the possibility that the unidentified genotypes belonged to the national genotype were considered high.